Coupled Pacific Rim megadroughts contributed to the fall of the Ming Dynasty’s capital in 1644 CE - Chen, Feng (2024)
Historical documents provide evidence for regional droughts preceding the political turmoil and fall of Beijing in 1644 CE, when more than 20 million people died in northern China during the late Ming famine period. However, the role climate and environmental changes may have played in this pivotal event in Chinese history remains unclear. Here, we provide tree-ring evidence of persistent megadroughts from 1576- 1593 CE and 1624-1643 CE in northern China, which coincided with exceptionally cold summers just before the fall of Beijing. Our analysis reveals that these regional hydroclimatic extremes are part of a series of megadroughts along the Pacific Rim, which not only impacted the ecology and society of monsoonal northern China, but likely also exacerbated external geopolitical and economic pressures. This finding is corroborated by last millennium reanalysis and numerical model simulations revealing internally driven Pacific sea surface temperature variations and the predominance of decadal scale La Niña-like conditions to be responsible for precipitation decreases over northern China, as well as extensive monsoon regions in the Americas. These teleconnection patterns provide a mechanistic explanation for reoccurring drought spells during the late Ming Dynasty and the environmental framework fostering the fall of Beijing in 1644 CE, and the subsequent demise of the Ming Dynasty.